Correlation between glomerular filtration rate with gamma camera and estimated serum creatinine clearance from Cockcroft and Gault's formula - Bhushan, Shivanand (Medknow Publications & Media Pvt Ltd, 2012)
PURPOSE OF THE STUDY: The purpose of the present study is to find out the correlation between the glomerular filtration rate (GFR by Gates gamma camera method) and serum creatinine clearance (SCrCl by Cockcroft and Gault's method) within ± 3 weeks’ time difference. MATERIALS AND METHODS: Study design retrospectively in 59 patients with serum creatinine value calculated for SCrCl with Cockcroft and Gault's formula as an index parameter for kidney function underwent the 99m-Technitium labeled Di-ethyl Triamine Penta Acetic Acid (99mTc-DTPA) renogram with ECIL planar gamma camera. RESULTS: All data of 59 patients has been divided into Group- I, II, and III based on the time difference of serum creatinine test from 99mTc-DTPA renal GFR tests performed on the same subjects. Serum Creatinine test was carried out within ± 3 days, between ± 4 days and ± 7 days, and between ± 8 days and ± 21 days from the DTPA GFR Test performed in the Group-I, II, and III respectively. Correlation coefficient of Group-I (n = 15) patients showed 0.8198 and P value < 0.001 for GFR and S. Creatinine within ± 3 days. Group-II (n = 17) and Group-III (n = 27) patients having correlation coefficient 0.6194 and 0.589 and P value <0.01 respectively, within ± 21 days. The two methods gave almost identical estimate of GFR even at 3 weeks interval. CONCLUSIONS: Study concludes that SCrCl using Cockcroft and Gault's formula could serve as an instant, easy, and reliable method for assessing kidney function. SCrCl with Cockcroft and Gault's formula is more useful for rapid estimation of global GFR for those patients who are not accessible to DTPA renogram with gamma camera. Correlation can be established further with the prospective study in various renal pathophysiological conditions.